THE ACTOR NETWORK MODEL IN THE DEVELOPMENT OF TOURISM IN THE TOURIST VILLAGE OF WONOLOPO, MIJEN DISTRICT, SEMARANG CITY - Genta Paradise Purba; Tri Yuniningsih; Ida Hayu Dwimawanti (Journal of Public Policy and Management Review, 2021)
Abstract Mayor's Decree Number 556/407 The Mayor of Semarang in 2012 became the basis for the determination of Wonolopo Village as a Tourism Village in the City of Semarang. This study aims to identify actors, analyze the roles of actors and describe the actor network models formed in the tourism development policy program in Wonolopo Tourism Village. The research method used is qualitative descriptive type with data collection methods direct / online interviews, observation and documentation. The results of this study indicate that DISBUDPAR Semarang City becomes the primary actor and acts as a policy cerator, facilitator and coordinator. The primary actors are POKDARWIS, RW, and Active Society as implementers and accelerators. Secondary actors are Mass Media and Academics act as accelerators. Tertiary actors are the District, Kelurahan and PKK acting as accelerators. The quaternary actor is the Passive Society, which acts as the target group and beneficiaries. The actor network model that is formed is the Quadruple Helix Model (Government, Academics, Society and Mass Media). The actor network that has been formed has not run optimally because some of the actors involved have not coordinated and communicated well in carrying out their respective roles. Recommendations are the need for coordination and communication by DISBUDPAR through the holding of meetings between actors to optimize the role of each actor involved and the involvement of the younger generation as a step to increase community participation in tourism promotion. Keywords: